2001
DOI: 10.1128/iai.69.5.3359-3371.2001
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection withBorrelia burgdorferiand the Agent of Human Granulocytic Ehrlichiosis Alters Murine Immune Responses, Pathogen Burden, and Severity of Lyme Arthritis

Abstract: Lyme disease and human granulocytic ehrlichiosis (HGE) are tick-borne illnesses caused by Borrelia burgdorferi and the agent of HGE, respectively. We investigated the influence of dual infection with B. burgdorferi and the HGE agent on the course of murine Lyme arthritis and granulocytic ehrlichiosis. Coinfection resulted in increased levels of both pathogens and more severe Lyme arthritis compared with those in mice infected with B. burgdorferi alone. The increase in bacterial burden during dual infection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
101
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 78 publications
2
101
0
5
Order By: Relevance
“…A study of A. phagocytophilum and B. burgdorferi showed that coinfection resulted in an increased bacterial burden in experimentally infected lab mice, which in turn resulted in higher numbers of B. burgdorferi bacteria in Ixodes scapularis ticks that fed on these mice (14), whereas in another study coinfection did not affect the acquisition of the two agents, and they were transmitted independently and with equal efficiency in coinfections and single infec- tions (28). We did not detect any increased bacterial burden in coinfected compared to singly infected animals in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of A. phagocytophilum and B. burgdorferi showed that coinfection resulted in an increased bacterial burden in experimentally infected lab mice, which in turn resulted in higher numbers of B. burgdorferi bacteria in Ixodes scapularis ticks that fed on these mice (14), whereas in another study coinfection did not affect the acquisition of the two agents, and they were transmitted independently and with equal efficiency in coinfections and single infec- tions (28). We did not detect any increased bacterial burden in coinfected compared to singly infected animals in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this scenario, coinfections with B. burgdorferi sensu lato and A. phagocytophilum in vertebrate hosts, as well as in ticks, are typically more common than expected from just random co-occurrence (reviewed by Nieto and Foley in 2009 [13]). The reason for the higher incidence of coinfections might be that A. phagocytophilum modifies the immune responses and thereby causes sensitivity to B. burgdorferi infection, as has been experimentally demonstrated (14,15).…”
mentioning
confidence: 99%
“…Abstr. Book, p. 52,2000). For clarity, this pathogen will be referred to as the HGE agent or simply Ehrlichia sp.…”
mentioning
confidence: 99%
“…2 While its epidemiologic and public health significance remain to be fully defined, HGE has been responsible for hundreds of cases and several fatalities. [3][4][5][6][7][8][9][10] Clinical information on HGE in children is limited to individual case reports. 4,8 Treatment in children is complicated because doxycycline, the antibiotic of choice, may cause permanent staining of the teeth in children younger than 8 years of age.…”
mentioning
confidence: 99%